Russia gets the blues : music, culture, and community in unsettled times - Urban, Michael E., 1947- (Culture and society after socialism., 2004)
Michael Urban chronicles the advent of blues music in Russia and explores the significance of the genre in the turbulent, postcommunist society. Russians, he explains, have taken a music originating in the "low" culture of the American South and transformed it into an object of "high" culture, fashioning a social identity that distinguishes blues adherents from both the discredited Soviet past and the vulgar consumerism associated with the country's Westernization. While adapting the idiom to their own conditions, Russia's bliuzmeny (bluesmen) have absorbed the blues ethos encoded in the music by their American forebears, using it to invert their social world, thus deriving dignity and satisfaction from those very things that give one the blues. Based on more than forty interviews with blues musicians and fans, nightclub managers, and others, Russia Gets the Blues reveals the fascinating history of blues in Russia, from the initial mimicry of British blues-rock to the recent emergence of a specifically "Russian blues." The gradual mastering of the idiom in Russia has been conditioned by the culture of the country's intelligentsia, a fact explaining why, on one hand, bliuzmeny feel compelled to proselytize on behalf of the music, to share with others this treasure of "world culture," while, on the other, they perform blues almost exclusively in English-which almost no one understands-and condemn any and all efforts to make the music commercially successful